Lam zab bla ma sgrub paʼi chos skor : a cycle of Buddhist practices focussing upon the realization (sādhana) of the guru - Chos-kyi-grags-pa, ʼBri-guṅ Rig-ʼdzin, b. 1595 (Khetsun Sangpo, 1976)
Meditational practices of the Drikurng Kargyudpa tradition.